2017
DOI: 10.1016/j.celrep.2017.01.020
|View full text |Cite
|
Sign up to set email alerts
|

EBI2 Is Highly Expressed in Multiple Sclerosis Lesions and Promotes Early CNS Migration of Encephalitogenic CD4 T Cells

Abstract: Arrival of encephalitogenic T cells at inflammatory foci represents a critical step in development of experimental autoimmune encephalomyelitis (EAE), the animal model for multiple sclerosis. EBI2 and its ligand, 7α,25-OHC, direct immune cell localization in secondary lymphoid organs. CH25H and CYP7B1 hydroxylate cholesterol to 7α,25-OHC. During EAE, we found increased expression of CH25H by microglia and CYP7B1 by CNS-infiltrating immune cells elevating the ligand concentration in the CNS. Two critical pro-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
128
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(133 citation statements)
references
References 38 publications
4
128
1
Order By: Relevance
“…Furthermore, EBI2‐expressing cells are abundant in MS lesions, and EBI2 positive T cells have been found in the inflamed white matter. In addition, analysis of different human T cell subsets revealed that human Th17 cells are almost completely EBI2 positive and express high levels of this protein compared to other T cell subsets . Functionally, human Th cells migrate toward 7α,25‐OHC in an EBI2‐dependent manner similar to murine Th cells …”
Section: Ebi2 In Local Immunity and Autoimmune Diseasesmentioning
confidence: 96%
See 3 more Smart Citations
“…Furthermore, EBI2‐expressing cells are abundant in MS lesions, and EBI2 positive T cells have been found in the inflamed white matter. In addition, analysis of different human T cell subsets revealed that human Th17 cells are almost completely EBI2 positive and express high levels of this protein compared to other T cell subsets . Functionally, human Th cells migrate toward 7α,25‐OHC in an EBI2‐dependent manner similar to murine Th cells …”
Section: Ebi2 In Local Immunity and Autoimmune Diseasesmentioning
confidence: 96%
“…Though, no difference in EAE onset and severity could be observed in mice lacking EBI2. However, using a transfer model of the disease, in which encephalitogenic T cells were transferred to other naïve mice, a robust delay of disease onset was observed using T cells lacking EBI2 (Fig. ).…”
Section: Ebi2 In Local Immunity and Autoimmune Diseasesmentioning
confidence: 98%
See 2 more Smart Citations
“…, EBI2-FL-EGFP (63), and EBI2-FL-EGFP 2D2 mice were bred at the Institute for Molecular Medicine at the University Medical Center of the Johannes Gutenberg-University Mainz. All mouse lines were on a pure C57BL/6 background.…”
Section: Rag1 -/-mentioning
confidence: 99%